Facile Adjustment of Exposed Crystal Facet of Hematite Derived-From Goethite to Enhance Cr (VI) Sorption - Yuxin Li; Guocheng Lv; Limei Wu; Zhaohui Li; Libing Liao (Crystals, 2023)
The (110) facets of hematite have excellent adsorption performance for chromium. We aim to obtain hematite with a large specific surface area and exposed (110) facets by using natural needle-like goethite as the precursor. The derived hematite shows a significant increment in the removal capacity of chromium by six times compared with goethite under the same experimental conditions. Structural model fitting of extended X-ray absorption fine structure (EXAFS) spectroscopy suggested that the interatomic distance of Cr-Fe was approximately 3.6 Å for the Cr (VI) coordinated hematite with exposed (110) facets, which was characteristic of the form of bidentate binuclear surface complex. Molecular dynamic simulations for the arrangement of Cr (VI) in (110) facets of goethite and hematite indicated the superiority of hematite adsorption for chromium. We optimized efficient and economic permeable reactive barrier (PRB) materials by crystal plane adjustment based on these experimental and theoretical results. It was found that the life span of the column even reached 610 PVs when the initial concentration of Cr (VI) was 20 mg/L, which indicates its potential application in the field of PRB medium material.